The impact of Immunomodulators on Reactivity the immune System cells in Model Vaccinal process against Tularemia - A. L. Kravtsov; S. N. Klyueva; S. A. Bugorkova (Эпидемиология и вакцинопрофилактика, 2016)
Investigated is the effect of azoximer bromide (polioxidonium - PO) and dalargin (DA) on the immune system cell reactivity in the anti-tularemia vaccine prosess modeling in Balb/c mice. The animals were immunized subcutaneously with a dose of 104 live microbial cells of vaccine strain Francisella tularensis 15 NIIEG. PO or DA subcutaneously administered 60 min before vaccination, respectively, in doses of 4 mg and 2 mg. On 3rd and 21st days of immunogenesis the peripheral organs of the immune system and the contents of the abdominal cavity were investigated. Cell response to vaccination and investigated immunomodulators evaluated by flow cytometry (CyAn ADP) for two light scatter parameters and for changing the proliferating and apoptotic cell number. Additionally, for the characterization of changes in the functional status of lymphocytes nuclei the light microscopy was used and titers of specific antibodies were determined. Installed is the different response of intact mice lymphocytes and phagocytes to PO and DA introduction. As distinct from PO, DA stimulated the lymphocete proliferation and macrophage apoptosis by acting on their cytoplasmic granules. PO activated the migration of phagocytes with high cytoplasmic granules from mice abdominal cavity in the spleen. Only when using the PO as an immunomodulator in anti-tularemia vaccine process modeling recorded a significant increase in specific antibody titers against the background of a long-term functional splenocyte activation and macrophages reduced macrophage damage intensity in the spleen and abdomen.